PENGARUH BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA DOSEN TETAP UNIVERSITAS BUNDA MULIA - Oktafalia Marisa (Universitas Bunda Mulia, 2017)
Each person have a very unique characteristic, it makes every organization or companies should bring those differences into a right lane. One of the tool to lead the diferrences is organization culture. This research tries to find out the effect of organizational culture to works satisfaction. The sample of this research are the full timer lecturers works in Bunda Mulia University. The result of this research shown us that there is a posifif and significant effect of organizational culture to works satisfaction. The result of the research will provide a basic information about organizational culture in Bunda Mulia, what lecturer feel about that and how that’s change affected their performances. Hopefully this research could provided a comprehensif data to develop any research in the futureKeyword :Organization culture, lecturers, work satisfaction